Enantioselective and Regiodivergent Functionalization of N‐Allylcarbamates by Mechanistically Divergent Multicatalysis. Issue 35 (27th July 2016) - Richmond, Edward; Khan, Ismat Ullah; Moran, Joseph
Abstract: A pair of mechanistically divergent multicatalytic reaction sequences has been developed consisting of nickel‐catalyzed isomerization of N ‐allylcarbamates and subsequent phosphoric‐acid‐catalyzed enantioselective functionalization of the resulting intermediates. By appropriate selection of reaction partners, in situ generated imines and ene‐carbamates are mechanistically partitioned to yield opposing functionalized products. Formal α‐functionalization to give protected α‐arylamines is achieved upon enantioselective Friedel–Crafts reaction with arene nucleophiles, whereas formal β‐functionalization is achieved upon reaction with diarylimine electrophiles in an enantioselective Povarov‐[4+2] cycloaddition. Abstract : Simple divergence : A pair of mechanistically divergent multicatalytic reaction sequences has been developed consisting of nickel‐catalyzed isomerization of N ‐allylcarbamates and subsequent phosphoric‐acid‐catalyzed enantioselective functionalization of the resulting intermediates. Formal α‐functionalization to give protected α‐arylamines is achieved upon enantioselective Friedel–Crafts reaction with arene nucleophiles, whereas formal β‐functionalization is achieved upon reaction with diarylimine electrophiles in an enantioselective Povarov‐[4+2] cycloaddition.